2017
DOI: 10.18632/oncotarget.14546
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Fyn-related kinase in breast cancer cells is associated with promoter site-specific CpG methylation

Abstract: The triple-negative breast cancer subtype is highly aggressive and has no defined therapeutic target. Fyn-related kinase (FRK) is a non-receptor tyrosine kinase, reported to be downregulated in breast cancer and gliomas, where it is suggested to have tumor suppressor activity. We examined the expression profile of FRK in a panel of 40 breast cancer cells representing all the major subtypes, as well as in 4 non-malignant mammary epithelial cell lines. We found that FRK expression was significantly repressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…We examined the relationship between the expression of FRK with mesenchymal markers Vimentin ( VIM ), N-cadherin ( CDH2 ), fibronectin ( FN1 ), snail family transcriptional repressor 2 ( SNAI2 ), twist family bHLH transcription factor 1( TWIST1 ), and epithelial markers E-cadherin ( CDH1 ) and Keratin 18 ( KRT18 ), in breast cancer cell lines stratified under Basal B (BB), Basal A (BA) and luminal (LU) ( Supplementary Table 5 , Figure 10 ). We recently reported the level of FRK transcript was low in the basal B breast cancers as compared to Basal A and Luminal cells [ 40 ]. We found that the mean transcript expression of VIM , CDH2 , FN1 , and TWIST1 were higher in the basal B breast cancer cells with low FRK transcript levels as compared to Basal A and Luminal cells that harbor high FRK transcript levels (P<0.05; Figure 10B , 10D , 10F and 10H ).…”
Section: Resultsmentioning
confidence: 99%
“…We examined the relationship between the expression of FRK with mesenchymal markers Vimentin ( VIM ), N-cadherin ( CDH2 ), fibronectin ( FN1 ), snail family transcriptional repressor 2 ( SNAI2 ), twist family bHLH transcription factor 1( TWIST1 ), and epithelial markers E-cadherin ( CDH1 ) and Keratin 18 ( KRT18 ), in breast cancer cell lines stratified under Basal B (BB), Basal A (BA) and luminal (LU) ( Supplementary Table 5 , Figure 10 ). We recently reported the level of FRK transcript was low in the basal B breast cancers as compared to Basal A and Luminal cells [ 40 ]. We found that the mean transcript expression of VIM , CDH2 , FN1 , and TWIST1 were higher in the basal B breast cancer cells with low FRK transcript levels as compared to Basal A and Luminal cells that harbor high FRK transcript levels (P<0.05; Figure 10B , 10D , 10F and 10H ).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with those of a previous report that Fyn-related kinase is associated with methylation at specific CpG islands of the promoter site. 39 To ascertain the association between signaling mechanisms of miR-5088-5p and Fyn, an miR-5088-5p inhibitor and Fyn-overexpressing vector were used. EMT-and stemness-related markers suppressed by the miR-5088-5p inhibitor were restored upon Fyn overexpression (Figure 6F).…”
Section: Fyn Promotes Biogenesis Of Mir-5088-5p By Inducing Its Hypomethylationmentioning
confidence: 99%
“…For instance, in breast cancer cells, the methylation of CPG sites in the promoter region of tumor suppressor was observed, and DNA methylation decreased the expression of FRK in a subset of breast cancer cells (29).…”
Section: Discussionmentioning
confidence: 99%